Accounting for investments : fixed income securities and interest rate derivatives : a practioner's guide - Subramani, R. Venkata (John Wiley & Sons, 2011)
The financial crisis that started in mid-2007 resulted in the accounting standard setters and market regulators across the globe to come up with several proposals to modify the accounting standards